Kirschner’s Wires Fixation of Unstable Distal Radius Fractures in Children with the Kapandji Technique - Shrestha, Sabin; Shrestha, Dinesh Kumar; KC, Dipendra; Karki, Prateek; Yogi, Sushil (Journal of Nepalgunj Medical College, 2021)
Introduction: Unstable distal radius fractures in children have more tendencies to get displaced with conservative management resulting into deformity. This Kapandji technique of K-wire fixation is on rise to reduce and maintain these fractures in recent days. Aims: The aim of this study was to evaluate the effectiveness of the K-wires fixation in unstable distal radius fracture with Kapandji techniques. Methods: A cross-sectional observational study was conducted in Nepalgunj Medical College and Teaching Hospital, Kohalpur, Banke in unstable distal radius fracture in children with K-wires fixation using Kapandji method. Results: Twenty eight unstable distal radius fractures in children between 6 to 14 years of age were treated with one intrafocal K-wire and one or two extra focal K-wires to augment fixation. Immobilization of forearm with above elbow slab/cast for four to six weeks was enforced. K-wires were removed between four to six weeks of operation depending upon the union and followed prospectively for four months. The mean age of patients presented was 8.57± 1.79 years. This technique brought near anatomical reduction in all fractures. There was no reduction loss or remanipulation in any case. All fractures achieved union and functional outcome was excellent in 24 cases based on Modified Mayo Wrist Score. There was fewer complications like pin tract infection. Conclusion: This Kapandji technique of K-wire fixation, leverage reduction method, being an additional tool helps to achieve near anatomical alignment, and maintain reduction throughout the duration of healing. So it is an advantageous technique.